PLC SCADA Based Fault Identification and Protection for Three Phase Induction Motor - Venkatesan Loganathan; S. Kanagavalli; P.R. Aarthi; K.S. Yamuna (Institute of Advanced Engineering and Science, 2014)
Today overvoltage, over current, overload, over temperature, and under voltage are the most commonly occurred problems in protection circuits of induction motor. We usually design Protection circuits with components such as timers, contactors and current relays. In order to reduce the mechanical components usage we prefer to use Personal Computer (PC) and Programmable Logic Controller (PLC). In this method Induction motors current, voltage, Speed, temperature values and fault occurred history are monitored in PC with an Alarm Message during fault occurrence. PLC-based protection methods are costs less, provides higher accuracy with safe mode of operation when compared with the other protection systems.